PUBLIC PERCEPTION OF WASTE IN LUBUK BASUNG OLD MARKET, LUBUK BASUNG DISTRICT - dandi, rahma; khairani, khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to determine the public's perception of waste in the Old Market Lubuk Basung, Lubuk Basung District, The method used in this research is descriptive qualitative method. The research informants are the people around the old market of Lubuk Basung and the government of Nagari Lubuk Basung, and the data used are secondary data and primary data. The data analysis used in writing is descriptive qualitative that is describing the results of observations and interviews obtained, grouped by type and added with supporting information in explaining the results of the study. Based on the data obtained, the condition of the garbage in the old market of Lubuk Bausung was not clean, including the condition of temporary garbage shelters that were not clean and always scattered around the garbage bins, the condition of the streets with a lot of garbage scattered, the habits of traders who piled up garbage in the corners of the market and the habits of the people who Dispose of any garbage that has become a culture in the community around the old Lubuk Basung market.